In Vitro Activity of Cocoa Powder Extracts on Some Biomarkers Implicated in P. falciparum Malaria Pathogenesis - Seth Kwabena Amponsah; Nana Nim Dwumfour (Journal of Pharmacy and Nutrition Sciences, 2015)
Malaria is a public health concern in many developing countries, including Ghana, and efforts are being made to eradicate it. Extracts from natural products have been used in several malaria endemic areas for malaria prophylaxis and treatment. Natural cocoa powder has been reported to possess in vitro direct inhibitory on P. falciparum. This study investigated the effect of natural cocoa powder on inducible nitric oxide, TNF-α and IL-10, biomarkers that play different roles in malaria pathogenesis. Chloroform and ethylacetate fractions of cocoa powder were cultured together with phytohemagglutinin-stimulated peripheral blood mononuclear cells (PBMCs) for 24 hours at 37°C with 5% CO2. Cell free supernatants were harvested and assayed for iNO, TNF-α and IL-10. Inducible NO was determined by diazotization reaction developed by Griess. TNF-α and IL-10 were determined by ELISA. This study showed that TNF-α and iNO in phytohemagglutinin-stimulated PBMCs were significantly reduced by cocoa fractions (p < 0.05), but IL-10 levels did not change significantly (p > 0.05), although TNF-α is known to up-regulate IL-10.Apart from the documented direct inhibitory effect of cocoa powder on P. falciparum, it can be hypothesized that the antiplasmodial activity of unsweetened cocoa powder could also be due to its ability to significantly inhibit iNO and TNF-α, inflammatory substances implicated in severe malaria pathogenesis.